Flouting Maxim in Leave the World Behind Movie Analysis - Rosita Fadillah; Dona Rahayu Sugiharti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the types of flouting maxims found in the film Leave the World Behind (2023) and to identify the most dominant type. This study applies the Cooperative Principle proposed by Grice (1975), focusing on the flouting of four types of conversational maxims, namely flouting of quantity, flouting of quality, flouting of relation, and flouting of manner. This study uses a descriptive qualitative method. The data consist of utterances taken from the dialogues of the film, collected through observation and documentation techniques, which involved watching the film, reading the dialogue transcript, identifying utterances that contain flouting maxims, and classifying them according to Grice’s theory. The findings show that there are 27 instances of flouting maxims in the film, flouting of quantity accounts for 8 data (29.63%), flouting of quality for 4 data (14.81%), flouting of relation for 14 data (51.85%), and flouting of manner for 1 data (3.70%). Based on the finding the most dominant flouted maxim is relation. The implicatures generated from these flouted maxims reveal that the characters frequently use indirect speech to express rejection, concealment of information, frustration, suspicion, and fear.